Do precedents violate judicial independence? Misunderstandings from the incompression - Núñez Vaquero, Álvaro (2020)
This work aims to clarify, from the point of view of the analytical theory of law, the question of whether the existence of judicial precedents in a legal system necessarily implies a violation of the internal judicial independence (IJI). To answer the question, we will try to clarify the way in which the IJI is being understood to affirm that it would be affected by the presence of a system of precedents (SP’s). It will proceed as follows: First, it will start by making explicit the reasons why it is necessary to deal with this problem. Secondly, it will be specified what it means that there is a binding SP’s. Third, it will explain what judicial independence consists of, presenting the reasons that justify the IJI: respect for the will of the legislator and equality in the application of law. Next, I will present three aspects of the IJI that could clash with the presence of an SP’s. In the fourth section, it will be argued that an SP’s is less injurious to the IJI than attributing to each of the judges a non-revisable competence to establish how the law should be interpreted and applied. In the conclusions, it is pointed out that although there may be reasons against having a precedent system, the IJI is not one of them.